Health-related QoL and fatality in CHD patients: findings from a national cohort study, Turkey. (20th October 2021) - Emli Alpay, E; Dinc, G; Sakarya, S; Ergor, G; Sozmen, K; Ekinci, B; Unal, B
Abstract: Background: Although strong association between self-reported health and coronary heart disease (CHD) exists, health related quality of life (HRQOL) has not been conceptualized as a predictor for fatality in CHD patients. We investigated whether HRQOL may predict the risk of death in six years in CHD patients. Methods: There were overall, 614 of CHD cases in the national representative Chronic Diseases and Risk Factors Survey in Turkey, 2011. Baseline self-reported health data on EuroQol- 5 Dimension (EQ-5D) and a Visual Analog Scale (VAS) were used from the same survey. The cases were followed-up for all-cause and CHD specific fatality (ICD-10 diagnostic codes: I20- I25) through electronic health records by 2017. Kaplan Meier and Cox regression models were used for data analysis. Age and sex adjusted HRs [aHR 95% CIs] were estimated for having some or extreme problems in EQ5D domains and VAS. Results: Median follow-up years (IQR) was 6.46 (6.39-6.47). The number of deaths from all causes and CHD were 103 and 26, respectively. Age and sex adjusted HRs for all causes fatality were statistically significant for some or extreme problems in usual activities [2.48 (95%CI 1.60-3.83)], in pain/comfort [2.28 (95% CI 1.44-3.62)], in self-care [2.25 (95% CI 1.46-3.46)] and in mobility [1.85 (95% CI 1.16-2.96)]. Age and sex adjusted HRs for CHD specific fatality were statistically significant for some or extreme problems in self-care [3.45 (95% CI 1.48-8.07)] and pain/comfort [3.07(95% CI 1.19-7.93)]. VAS was negatively associated with overall fatality. Conclusions: In CHD cases, poor self reported health might be a good indicator for overall and CHD specific fatality in 6 years. Especially having some or extreme problems in selfcare and pain/comfort are closely related with overall fatality as well as CHD specific fatality. Key messages: There are strong relationships between HRQOL and all causes fatality as well as CHD specific fatality. Poor self- reported health might be a predictor for overall and CHD specific fatality in CHD cases.